An evaluation of parents as behavior change agents in the Preschool Life Skills program. Issue 2 (12th February 2020) - Gunning, Ciara; Holloway, Jennifer; Grealish, Leanne
Abstract : Parental involvement in intervention can support intervention efficacy, improve generalization, and increase accessibility. The Preschool Life Skills (PLS) program is designed to teach 13 preschool life skills and prevent problem behavior. The current study explores the utility of the PLS program as delivered by parents. In Experiment 1, 6 parents were taught to use the PLS program at home with their typically developing children (3 years 3 months to 4 years 11 months). This application of the PLS program led to an increase in preschool life skills and a decrease in problem behavior and supported some generalization of the target preschool life skills from the home to preschool settings. In Experiment 2, 7 parents were taught to use the PLS program with their children with autism spectrum disorder (ASD; 3 years 11 months to 6 years 9 months). Results overall supported the parent implementation of the program and highlighted modifications required to support positive outcomes for children with ASD.